DiCER: A distributed consumer experience research method for use in public spaces. Issue 81 (September 2015) - Gault, Paul; Masthoff, Judith; Johnson, Graham
Abstract: This paper presents research into new ways in which organisations can gather field-based consumer insight particularly in public spaces. In an increasingly complex and fast moving business world, there is a need for quicker and more efficient consumer experience research that also provides a wider focus on the situation under investigation as required when studying urban spaces. The paper presents a method called DiCER for using large groups of non-specialists (i.e non-ethnographers) to make fieldwork observations working in a transdisciplinary setting with ethnographers and designers. In this method, groups of people are given a small amount of training and provided with support materials that allow them to make and report observations. The method provides a way of harnessing the potential of an organisation׳s staff for a shared goal of generating useful fieldwork material. The method was first tried out in two studies that investigated how collaborative activity could be facilitated in large public spaces. This helped identify issues related to the design of support materials whilst conducting fieldwork and explored ways of analysing and presenting the results of such activity. A follow-up study observed the activity of conversations between strangers waiting in a railway station concourse. The aim of this was to test both the method on a more focused problem and prototype tools to support recording observations in such a context. The outcomes were prototypes and interventions demonstrating potential techniques for gathering fieldwork material. A final study explored the potential of using a group of non-specialist employees distributed across an organisation to fulfil parts of a fieldwork project. This guided the development of training sessions for people with little prior knowledge of doing fieldwork. The main output was design recommendations for further applications of the method in a similar context. Highlights: New design research method for understanding consumer experience in public spaces. Based on design ethnography and developed through four studies in public spaces. Supports collaboration of ethnographers, designers and non-specialist fieldworkers. Method has three phases of activity detailing training, divergence and convergence. Provides a framework and materials to facilitate fieldwork across a large group.